Hupresin Retains Binding Capacity for Butyrylcholinesterase and Acetylcholinesterase after Sanitation with Sodium Hydroxide - Onder, Seda; David, Emilie; Tacal, Ozden; Schopfer, Lawrence M.; Lockridge, Oksana (Frontiers in Pharmacology, 2017)
Hupresin is a new affinity resin that binds butyrylcholinesterase (BChE) in human plasma and acetylcholinesterase (AChE) solubilized from red blood cells. Hupresin is available from the CHEMFORASE company. BChE in human plasma binds to Hupresin and is released with 0.1 M trimethylammonium bromide with full activity and 10-15% purity. BChE immunopurified from plasma by binding to immobilized monoclonal beads has fewer contaminating proteins than the one-step Hupresin-purified BChE. However, when affinity chromatography on Hupresin follows ion exchange chromatography at pH 4.5, BChE is 99% pure. The membrane bound AChE, solubilized from human red blood cells with 0.6 % Triton X-100, binds to Hupresin and remains bound during washing with sodium chloride. Human AChE is not released in significant quantities with nondenaturing solvents, but is recovered in 1% trifluoroacetic acid. The denatured, partially purified AChE is useful for detecting exposure to nerve agents by mass spectrometry. Our goal was to determine whether Hupresin retains binding capacity for BChE and AChE after Hupresin is washed with 0.1 M NaOH. A 2 mL column of Hupresin equilibrated in 20 mM TrisCl pH 7.5 was used in 7 consecutive trials to measure binding and recovery of BChE from 100 mL human plasma. Between each trial the Hupresin was washed with 10 column volumes of 0.1 M sodium hydroxide. A similar trial was conducted with red blood cell AChE in 0.6% Triton X-100. It was found that the binding capacity for BChE and AChE was unaffected by washing Hupresin with 0.1 M sodium hydroxide. Hupresin could be washed with sodium hydroxide at least 7 times without losing binding capacity.